Microstructure, mechanical performance and corrosion properties of base metal solder joints - Sujesh Machha; M Vasanth Kumar; Azhagarasan; V Rangarajan (Wolters Kluwer Medknow Publications, 2011)
Context: Alloys have been considered to be of paramount importance in the field of prosthodontics. Long span prosthesis may often require joining of one or more individual castings to obtain better fit, occlusal harmony and esthetics in comparison to one-piece casting. Aim: This study was undertaken to evaluate the mechanical properties of base metal alloys joined by two different techniques, namely, gas oxygen torch soldering and laser fusion, compared to a one-piece casting. Mechanical properties evaluated were tensile strength, percentage of elongation and hardness of the solder joint. In addition, corrosion properties and scanning electron microscopic appearance of the joints were also evaluated. Materials and Methods: The samples were prepared according to American Society for Testing Materials specifications (ASTM, E8). Specimens were made with self-cure acrylic and then invested in phosphate-bonded investment material. Casting was done in induction casting machine. Thirty specimens were thus prepared for each group and compared with 30 specimens of the one-piece casting group. Statistical Analysis Used: SPSS software (version 10.0, Chicago, IL, USA) was used for statistical analysis. ANOVA and Benferroni post hoc tests were done for multiple comparisons between the groups and within the groups for mean difference and standard error. Results: Results showed that tensile strength of the one-piece casting was higher than laser fused and gas oxygen torch soldered joints. Laser fused joints exhibited higher hardness values compared to that of gas oxygen torch soldered joints. Scanning electron microscopic examination revealed greater porosity in the gas oxygen torch soldered joints. This contributed to the reduction in the strength of the joint. Gas oxygen torch soldered joints showed less corrosion resistance when compared to laser fused joints and one-piece casting. Conclusion: Laser fusion, which is a recent introduction to the field of prosthodontics, produces joints which have properties between those of one-piece casting and the gas oxygen torch soldering.